Halangan pelaksanaan SPC: satu pandangan praktikal daripada syarikat pengusaha kecil dan sederhana - Mohd Nizam Ab Rahman,; Rosmaizura Mohd Zain,; Nizaroyani Saibani,; Suriani Abdul Rahman ,; Zulkifli Mohd Nopiah , (Penerbit Universiti Kebangsaan Malaysia, 2010)

(untitled)
This study presents the outcome of case studies conducted in ten Malaysian Small and Medium Enterprises (SMEs) manufacturing companies (named as company A to J) by focusing on the obstacles or problems faced in the context of statistical process control (SPC) software or system application, particularly among production workers (operators). Furthermore, the data collection is carried out in stages through interviews, questionnaires, and observations with company representatives. The results show that there are several related barriers faced by the SMEs companies; these issues include top management support, commitment, costs to develop the system, as well as education and training of SPC. In addition, the study also revealed that manual SPC method is subjected to several limitations such as human errors and inefficient data management. In conclusion, several issues and practical reflection provided by SMEs would be used as a medium to further improve the SPC application in the future